OUTCOMES OF 5-ALA FLIORESCECE-GUIDED SURGERY FOR HIGH GRADE G - V. A. Byvaltsev; I. A. Stepanov; A. I. Kichigin (Сибирский онкологический журнал, 2018)
High grade gliomas (HGG) are the most aggressive primary brain tumors. The extent of resection (EOR) is proved to be an important prognostic factor in patients with HGG. There are no yet published studies on the use of fluorescent-guided resection using 5-aminolevulinic acid (5-ALA) in HGG surgery, based on the comparison of neuroimaging characteristics, intraoperative parameters and clinical outcomes. The purpose of this study was to analyze the results of 5-ALA fluorescent-guided resection in patients with HGG by comparing neuroimaging characteristics, intraoperative parameters and clinical outcomes. Material and methods. The study included 48 patients (30 men and 18 women) aged 35 to 76 years (mean age 47.3 ± 8.4 years) with newly diagnosed HGG. The patients underwent fluorescent-guided surgery that permitted the intraoperative visualization of malignant glioma tissue and supported the neurosurgeon with real-time guidance for differentiating tumor from normal brain. The Karnofsky performance status (KPS) was assessed. Results. The maximum EOR (90–98 %) was achieved in 40 (83.3 %) patients with newly diagnosed HGG. The maximum EOR was performed in 28 (58.3 %) patients with glioblastomas and in 12 (25 %) patients with grade III gliomas (p=0.408) In addition, the maximum EOR was achieved by microneurosurgical removal of 9 (18.75 %) HGGs having a volume of ≥9 cm3 and 21 (43.75 %) of HGGs with a volume<9 cm3 (p=0.029). The tumor boundaries detected by neuronavigation differed by fluorescence data in 28 (58.3 %) patients The divergence between neuronavigation and 5-ALA fluorescence was reported in 19 (39.5 %) patients with glioblastomas and in 3 (6.25 %) patients with grade III gliomas (p=0.014); and in 9 (39.5 %) and in 14 (29.1 %) patients affected with larger (≥9 cm3 ) and smaller (<9 cm3 ) tumor, respectively (p=0.677). Overall, 36 (75 %) patients experienced an improvement in their KPS score, 9 (18.75 %) remained stable, and 3 (6.25 %) declined. Conclusion. The use of 5-ALA fluorescence in surgery for HGG makes it possible to achieve the gross total resection in most cases. The localization of HGGs and their size are the most important factors in achieving maximum EOR. Key words: high grade gliomas, fluorescent navigation, 5-aminolevulinic acid, extent of tumor resection><9cm3 ) tumor, respectively (p=0.677). Overall, 36 (75 %) patients experienced an improvement in their KPS score, 9 (18.75 %) remained stable, and 3 (6.25 %) declined. Conclusion. The use of 5-ALA fluorescence in surgery for HGG makes it possible to achieve the gross total resection in most cases. The localization of HGGs and their size are the most important factors in achieving maximum EOR.